NGC2587: a sparse open cluster projected on to a populous star field - Piatti, Andres Eduardo (2009)
We present CCD photometry in the Johnson U, B and V and Kron–Cousins I passbands for the open cluster NGC 2587. The sample consists of 4406 stars reaching down to V∼ 21.0. We developed a new method to clean statistically the colour–magnitude diagrams. NGC 2587 appears to be a sparse, relatively bright open cluster, with a few tens of members projected on to a populous star field. The comparatively bright F7/8 II type star HD 70927, located close to the cluster centre, seems not to be a member. Our analysis suggests that NGC 2587 is slightly younger than the Hyades and probably of solar metallicity. A cluster radius of roughly 8 arcmin was estimated from the radial stellar density profile. From 18 probable cluster members with measured proper motions, we derive the following mean values for NGC 2587: μα=−4.3 ± 3.6 mas yr−1 and μδ=−2.5 ± 3.4 mas yr−1. Adopting the theoretical metal content Z= 0.02, which provides the best global fit, we derive a cluster age of 500+60−50. Simultaneously, colour excesses E(B−V) = 0.10 and E(V−I) = 0.15 and an apparent distance modulus of V−MV= 12.50 are obtained. The interstellar extinction in the cluster direction is found to follow the normal law. NGC 2587 is located at a distance of (2.70 ± 0.70) kpc from the Sun and ∼9.8 kpc from the Galactic centre.